PERAN PEMERINTAH DAERAH DALAM PELAKSANAAN URUSAN WAJIB LINGKUNGAN HIDUP (STUDI UPAYA PENGELOLAAN LIMBAH B3 DI KABUPATEN SIDOARJO) - Galih Wahyu Pradana; Alifiah Tri Setya Cahyandari (Publika, 2022)
The COVID-19 pandemic in Indonesia is closely related to increase infectious waste produced by medical personnel and the public. If many people are infected COVID-19, the hospitals capacity can impact and the amount of infectious waste generated is increase. Infectious waste includes in the B3 waste category, which contains hazardous and toxic materials that can pollute, damage, and endanger the environment, health, and the survival of living things. Sidoarjo Regency which ever be a red zone area for the spread of COVID-19, certainly unavoidable from the problem of B3 waste. With the increase in that amount of B3 waste, the government role is needed to fulfill the precautionary principle and proximity principle of B3 waste management. The regional government through DLHK Sidoarjo as the executor of mandatory environmental affairs need to answer the issues of B3 waste management at the regional level. The focus of this research uses Sondang P. Siagian government role theory which highlights the government role as a stabilizer, innovator, modernizer, pioneer, and self implementer. By using descriptive research methods and qualitative approaches, the results show that the government has fulfilled its role, it’s just some of the methods need to be improvement , and awareness from the public or business actors/activities needed to minimize the usage of tools or materials that can generate B3 waste.